Children’s Motivation to Learn at Home During the COVID-19 Pandemic: Insights From Indian Parents - Mak, Matthew H. C. (Frontiers in Education, 2021)
The COVID-19 pandemic has forced millions children worldwide to learn at home. Recent reports showed that it had a negative impact on children’s motivation to learn. The current study aimed to investigate what factors are associated with a child’s motivation during the pandemic and how parents motivated their children to learn at home. A total of 1,041 parents from India filled out a close-ended survey to help shed light on the issues. The results confirmed that children in India are significantly less motivated to learn during (vs. before) the pandemic and revealed that a child’s motivation to learn at home is associated with multiple factors, such as household income, parents’ employment status, child’s academic achievement, and parent’s enjoyment in homeschooling. Interestingly, the availability and usage of various technological resources bear no relation to a child’s motivation. Finally, parents in India most frequently used TV time, words of encouragement, and play/game time as motivators; the least popular motivators were money, new toys, and physical punishment. Exploratory analyses showed that a child’s motivation to learn tends to be lower when parents used more physical punishment to “motivate” their children. These findings were discussed in relation to public/education policies.